How do you solve x^2 + 6x + 10 = 0 by completing the square?

2 Answers
Apr 3, 2016

(x+3)^2 + 1 -> x = +-i - 3

Explanation:

Completing the square is a method of getting as close as you can with one set of brackets and adding or subtracting the rest.

It ends up in a form like

x^2 + ax + b = (x + c)^2 + d

c is always half of a, so that when you expand out the brackets you have the right coefficients for x^2 and x.

a = 6 -> c = 3
(x + 3)^2 = x^2 + 6x + 9

As you can see this is pretty close to the original quadratic. All you need to do is add 1 and it equates perfectly.

x^2 + 6x + 10 = (x+3)^2 + 1

To then solve, rearrange like so

(x + 3)^2 + 1 = 0
(x + 3)^2 = -1
x + 3 = sqrt(-1) = +-i
x = +-i - 3

Apr 3, 2016

There is no solution for the given equation for any x in the set of 'Real Numbers'.

color(blue)(x=-3+-i)

Explanation:

Consider the standard form of y=ax^2+bx+c

The by completing the square we have:

y=a(x+b/(2a))^2 +c - [(b/(2))^2]

In your case a=1 so we have:

y=(x+b/2)^2+c-[(b/2)^2]

=>y=(x+3)^2+10 -(3^2)

=> y= (x+3)^2+1
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
x_("vertex") = (-1)xx(+3) = -3
y_("vertex") =+1

The coefficient of x^2 = +1 so the graph is of shape type uu

Thus the vertex is a minimum and above the x-axis

Thus there is no solution for x at y=0 where x in RR

However their will be a solution for x in CC (Complex numbers)

Given that 0=(x+3)^2+1

=> sqrt((x+3)^2)=sqrt(-1)

=>+-(x+3)= i

Updated: The +- is for the x" and " 3. Not for the i

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(brown)("Suppose we had "-(x+3)= i

This becomes: -x-3=i

=> -x=+3+i
Multiply by (-1)

color(blue)(=>+x=-3-i)
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

color(brown)("Suppose we had "+(x+3)= i)

This becomes: x=-3+i

color(blue)(=>+x=-3+i)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

Solution for x at y=0 is

color(magenta)(x=-3+-i)

Tony B